What drives trust of long-term unemployed in their caseworkers? An empirical analysis using experimental data - Joachim Wilde (Osnabrück University, Institute of Empirical Economic Research, 2020)
Overcoming long-term unemployment is a challenging task in which trust of the long-term unemployed in their caseworkers is a key issue. However, research about drivers of this trust is a white spot in the literature. The paper closes this gap. Embedded in a theoretical model at the organizational level a trust game with real long-term unemployed and caseworkers is evaluated empirically. The results support the social identity theory, i.e. trust in members of the "own" group is higher than trust in the members of the "other" group, as well as more traditional explanations of trust. The results are used for policy conclusions.
Keywords: C25; C91; J64; J68; 330; trust; long-term unemployment